Integrating Islamisation and virtue in iCGPA at IIUM - Mat Ghani, Gairuzazmi; Borhan, Lihanna; Sarudin, Isarji (2017)
International Islamic University Malaysia (IIUM), Garden of Knowledge and Virtue (Taman Ilmu dan Budi), aims to produce quality intellectuals, professionals and scholars by integrating the qualities of faith (iman), knowledge (`ilm), and good character (akhlaq) to serve as agents of comprehensive and balanced progress. This paper describes the implementation of iCGPA at IIUM and the integration and measurement of faith, knowledge and good characters. The main focus of this paper is on Islamisation and the fourth learning outcome domain of values, attitudes and professionalism, which has been renamed as Budi or Virtue.